Efektivitas Model Pembelajaran Project Based Learning terhadap Keterampilan Menulis Kreatif Siswa Sekolah Dasar - Khabibah, Novia Putri Nurul; Munir, Muhammad Misbahul (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study examines how Project Based Learning (PjBL) affects the creative writing ability of grade V students at SDN 1 Krasak Bangsri Jepara. Creating a more engaging learning environment can encourage creativity and improve students' writing skills.Method – Experimental quantitative research was used in this study. The research design was pre-experimental with one group, namely pretest-posttest. This study involved 29 5th grade students of SDN 1 Krasak Bangsri. Tests, observations, interviews, and documentation were used to collect data, with assessment of creative writing skills at the beginning and end of the project. Findings – This study shows that the application of the Project Based Learning (PjBL) model significantly improves the creative writing ability of grade V students of SDN I Krasak Bangsri Jepara, with the pretest average score increasing from 62.1 to 84.5 on the posttest, resulting in an average difference of 22.4. The analysis showed a significant difference between pretest and posttest scores, indicating the effectiveness of PjBL. Effect Size analysis using Cohen's d confirmed the high effectiveness of this model, which opens up opportunities for learning innovation in elementary schools. PjBL can be adapted by teachers to create an interactive learning environment and stimulate students' creativity. Research Implications – These findings suggest that PjBL encourages active participation, creativity, and the development of structured writing. However, the generalizability of this study is limited due to the absence of a control group and the relatively short intervention period. In addition, individual characteristics such as students' motivation and previous writing experience may have influenced the results of the study. Therefore, further research with a larger sample size and diverse measurement techniques is needed to gain a more comprehensive understanding of the effectiveness of PjBL in different educational contexts.